A comprehensive analysis of microRNAs as diagnostic biomarkers for asthma - Xu, Li (Ther Adv Respir Dis, 2020)
BACKGROUND: It is unclear whether microRNAs could be a potential diagnostic biomarker for asthma or not. The objective of this study is to figure out the diagnostic value of microRNAs in asthma. METHODS: Literature retrieval, screening of publications, specific data extraction, and quality evaluation were conducted according to the standard criteria. Stata 14.0 software was used to analyze the diagnostic value of microRNA for asthma, including the combined sensitivity (Sen), specificity (Spe), the area under the curve (AUC), positive likelihood ratio (PLR), negative likelihood ratio (NLR), and diagnostic odds ratio (DOR). RESULTS: A total of 72 studies, containing 4143 cases and 2188 controls, were included for this comprehensive analysis. None of the included publications were rated low in quality. We summarized that, compared with controls, more than 100 miRNAs were reported differently expressed in asthma, although the expression trends were inconsistent. Besides, there were five studies among these 72 articles that applied the diagnostic evaluation of microRNAs in asthma. We found that the pooled Sen, Spe, and AUC for the combination of miR-185-5p, miR-155, let-7a, miR-21, miR-320a, miR-1246, miR-144-5p, and miR-1165-3p in asthma were 0.87 (95%CI: 0.72–0.95), 0.84 (95%CI: 0.74–0.91), and 0.93 (95%CI: 0.89–0.94) individually, and the PLR, NLR, and DOR were 5.5 (95%CI: 3.1–9.7), 0.15 (95%CI: 0.07–0.36), and 35 (95%CI: 10–127) in asthma, respectively. In terms of subgroup analyses, we found that the Sen for these combination miRNAs from serum was higher than that in plasma, while the Spe in plasma worked better than that in serum. Furthermore, compared with children, the combination of above miRNAs from adults had higher Spe and similar Sen. CONCLUSIONS: From our analysis, the combination of miR-185-5p, miR-155, let-7a, miR-21, miR-320a, miR-1246, miR-144-5p, and miR-1165-3p from peripheral blood could potentially act as a diagnostic biomarker for asthma. The reviews of this paper are available via the supplemental material section.